Autoradiographic imaging and quantification of the high-affinity GHB binding sites in rodent brain using3H-HOCPCA - Klein, A B; Bay, T; Villumsen, I S; Falk-Petersen, C B; Marek, A; Frølund, B; Clausen, R P; Hansen, H D; Knudsen, G M; Wellendorph, P (Neurochemistry international, 2016)
GHB (γ-hydroxybutyric acid) is a compound endogenous to mammalian brain with high structural resemblance to GABA. GHB possesses nanomolar-micromolar affinity for a unique population of binding sites, but the exact nature of these remains elusive. In this study we utilized the highly selective GHB analogue, 3-hydroxycyclopent-1-enecarboxylic acid (HOCPCA) as a tritiated version (3H-HOCPCA) to radioactively label the specific GHB high-affinity binding site and gain further insight into the density, distribution and developmental profile of this protein. We show that, in low nanomolar concentrations,3H-HOCPCA displays excellent signal-to-noise ratios using rodent brain autoradiography, which makes it a valuable ligand for anatomical quantification of native GHB binding site levels. Our data confirmed that3H-HOCPCA labels only the high-affinity specific GHB binding site, found in high density in cortical and hippocampal regions. The experiments revealed markedly stronger binding at pH 6.0 (Kd73.8 nM) compared to pH 7.4 (Kd2312 nM), as previously reported for other GHB radioligands but similar Bmaxvalues. Using3H-HOCPCA we analyzed the GHB binding protein profile during mouse brain development. Due to the high sensitivity of this radioligand, we were able to detect low levels of specific binding already at E15 in mouse brain, which increased progressively until adulthood. Collectively, we show that3H-HOCPCA is a highly sensitive radioligand, offering advantages over the commonly used radioligand3H-NCS-382, and thus a very suitable in vitro tool for qualitative and quantitative autoradiography of the GHB high-affinity site.
Keywords: cyklopentany; Animals; kyseliny karboxylové; Carboxylic Acids; Cyclopentanes; vazebná místa; Rodentia; hydroxybutyráty; Binding, Competitive; Mice; mozek; myši; kompetitivní vazba; Brain; Autoradiography; radioligandová zkouška; hlodavci; Radioligand Assay; zvířata; Hydroxybutyrates; autoradiografie; Binding Sites